Nutrition in patients with unilateral neglect - Di Simone, Emanuele; Giannetta, Noemi; Gazzelloni, Andrea; Torre, Roberto; Livadiotti, Jacopo; Dionisi, Sara; Di Muzio, Flavio; Montesano, Marzietta; Moriconi, Alessandra; Fabbian, Fabio; Di Muzio, Marco (Progress in Nutrition, 2020)
Objective: to evaluate the impact of neglect on patient nutrition and nursing skills to reduce malnutrition. To determine attitude of health care professionals towards nutritional needs in patients with neglect.Methods: The purpose of this narrative literature review was to explore empiric literature that surrounds the measures to be carried into the environment of the meal, diet and encourages patient independence with neglect. This literature review to include articles from all countries and national languages (English, Spanish and Italian) that pertain to this topic. Methods OVID Medline, CINAHL, Cochrane, Scopus, Google Scholar and Web of Science were used to identify articles. Twenty-five articles were included according to inclusion and exclusion criteria.Results: The review shows that damage to the right cerebral hemisphere leads to a higher frequency of dysphagia than lesions in the left cerebral hemisphere. The lack of awareness of the stimuli coming from one side of the space, caused in fact by the neglect, make the feeding of the patient difficult and lead to inhalation and aspiration pneumonia.Conclusions: Dysphagia contributes to more difficult rehabilitation: patients with neglect have a high risk of developing malnutrition, reduced immune defenses, infections and aspiration pneumonia.